2012
DOI: 10.1016/j.jas.2011.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Faecal biomarker and archaeobotanical analyses of sediments from a public latrine shed new light on ruralisation in Sagalassos, Turkey

Abstract: a b s t r a c tA public latrine in the 'Imperial Baths' of Sagalassos was transformed into a dump site in the early Byzantine period. Several layers of urban waste, including ceramics, bones, glass and perhaps excrements were deposited on the floor. Faecal biomarker analyses and archaeobotanical analyses were conducted to reconstruct the history of the room. 5b-stanols of human origin, such as coprostanol, were found in the sewage channels together with mineralised plant remains, indicating a human faecal cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 67 publications
1
32
0
1
Order By: Relevance
“…Especially coprostanol and epicoprostanol are biomarkers for faeces from an omnivore [65]. This is not surprising as the pot was recovered from a latrine.…”
Section: Resultsmentioning
confidence: 92%
“…Especially coprostanol and epicoprostanol are biomarkers for faeces from an omnivore [65]. This is not surprising as the pot was recovered from a latrine.…”
Section: Resultsmentioning
confidence: 92%
“…The presence of both 5β‐stigmastanol and DCA at all depths within the soil section could be due to one of two factors. Baeten et al () observed migration of both stanols and bile acids in archaeological soils. They suggested that due to the solubility of bile acids, they are prone to leaching.…”
Section: Resultsmentioning
confidence: 99%
“…Organic compounds, sourced from people and animals, lend themselves to relatively easy detection in the bioturbated sediments, with such materials persisting for millennia (e.g., Bull et al ; Baeten et al ), which offers a contrast to transhumance control sediment recovered in younger beds described in Part I. We can hypothesize that Hannibal's army may have produced the unusual non‐laminated, massively churned‐up sediment during passage over the Alps.…”
Section: Introductionmentioning
confidence: 99%
“…However, the eggs of some helminths of animals appear similar to those of humans, for example, roundworm and whipworm in pigs (Ascaris suis and Trichuris suis) produce eggs microscopically indistinguishable to roundworm and whipworm in humans (A. lumbricoides and T. trichiura). The most reliable technique to identify the species of origin of a coprolite is the detection of bile acids and sterols within the coprolite with mass spectrophotometry, as different animals produce different kinds of bile acids and sterols (Shillito et al, 2011;Baeten et al, 2012). However, this relatively new technique is not currently being widely applied to coprolite analysis due to its cost.…”
Section: Prevalence Of Parasites In the Pastmentioning
confidence: 99%